Mathematics, teachers and children - Pimm, David (London : Sydney : Hodder and Stoughton, 1988)
An Open University coursebook for mathematics teachers and teacher trainers designed especially to accompany course ME234 "Mathematical Thinking". It consists of a collection of articles and readings designed for those concerned with teaching primary and secondary mathematics.
Include index.
Keywords: Mathematics -- Study and teaching; Schools -- Curriculum subjects: Mathematics -- Teaching